The Contribution of Leadership Style and Organizational Culture on Teachers’ Performance at Vocational High School - Kamid, Kamid; Sabil, Husni; Syafmen, Wardi; Azzahra, Miftahul Zannah (Jurnal Pendidikan dan Pengajaran, 2022)
This study aims to determine the differences and also the relationship between student process skills and student responses to the jigsaw learning model in mathematics subjects at SD Negeri 156/I Bulian Baru, SD Negeri 04/I Sungai Ruan Ilir, MIS Nurul Jadid and MIS Nurul ihsan in Batanghari district. This research is important so that teachers or educators know the students' process skills and student responses to the jigsaw learning model. The urgency of this research is as a reference for educators in carrying out teaching so that it is more optimal by using the jigsaw learning model to improve students' process skills in mathematics subjects at SDN/MIS. This type of research is a quasi-experimental quantitative research by comparing 8 classes using a jigsaw model with material velocity and discharge. The sample in this study was 288 elementary school students, the sampling technique was purposive sampling. This study uses quantitative data analysis with the help of SPSS 25 statistics. Based on the correlation test of student process skills and student responses to the jigsaw model with speed and discharge material, there is a relationship between student process skills and student responses to the jigsaw model with speed and discharge material. The novelty of this study compared to previous research is to use the variables of student process skills and student responses to the jigsaw learning model.